2010
DOI: 10.1002/cyto.b.20580
|View full text |Cite
|
Sign up to set email alerts
|

Variation of MDR proteins expression and activity levels according to clinical status and evolution of CML patients

Abstract: The involvement of the multidrug resistance (MDR) mediated by ABC transporter proteins P-glycoprotein (Pgp) and multidrug resistance-associated protein-1 (MRP1) overexpressions in patients with chronic myeloid leukemia (CML) are not completely understood. Pgp and MRP1 expressions and activity were analyzed in samples from 158 patients with chronic myeloid leukemia (CML). Using flow cytometry, Pgp expression was more frequently observed in early chronic (P 5 0.00) and in advanced (P 5 0.02) CML phases when it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 26 publications
4
32
1
1
Order By: Relevance
“…However, drug resistance can also be acquired during the course of chemotherapy by tumors that are initially sensitive to treatment (8,9). To support this notion, we have recently shown that modifications in Pgp status, caused by a diversity of drugs, can alter the desirable effect induced by a specific chemotherapeutic drug during the treatment of chronic myeloid leukemia (CML) patients (10).…”
Section: Introductionmentioning
confidence: 99%
“…However, drug resistance can also be acquired during the course of chemotherapy by tumors that are initially sensitive to treatment (8,9). To support this notion, we have recently shown that modifications in Pgp status, caused by a diversity of drugs, can alter the desirable effect induced by a specific chemotherapeutic drug during the treatment of chronic myeloid leukemia (CML) patients (10).…”
Section: Introductionmentioning
confidence: 99%
“…13) Moreover, upregulation in the P-gp expression level in CML cells from patients has been reported to correlate with increased resistance to imatinib. 14,15) Very little information is available on the drug transporters involved in the disposition of nilotinib. In CML cells, the OCT inhibitor prazosin had no effect on the intracellular uptake of nilotinib.…”
mentioning
confidence: 99%
“…MDR1/P-gp is expressed in almost all human tumor cells to different degrees, and its expression in tumors insensitive to chemotherapy or with poor efficacy is often high (25). Previous studies have reported that the sensitivity of some cancer patients to chemotherapy was increased following the administration of P-gp inhibitors (24,(26)(27)(28). In the present study, downregulation of P-gp protein by naringin was also observed, and therefore it was inferred that the ameliorating effect of naringin on cisplatin resistance of ovarian cancer cells was associated with the downregulation of P-gp.…”
Section: Discussionmentioning
confidence: 99%